The international air carrier’s liability under the Warsaw Convention 1929 and its system - Mohd Bahrin Othman (Fakulti Undang - Undang, 2001)

(untitled)
The regime of liability governing international carriage by air has undergone the most radical transformation since the Warsaw Convention was adopted in 1929. One of the factors which contributed to the above measures was the perception in may quarters that the limits of liability under the Warsaw Convention were too low and that, with the failure of the United States Senate to ratify Montreal Protocol 3, the entire Warsaw Convention was vulnerable to demunciation by the United States government. Such denunciation would effectively abolish part of the framework which carries and their insurers have relied on to resolve claims arising in international transportation. This brief paper will discuss the development of the international air carrier’s liability regime under Warsaw Convention 1929 and the various alternatives initiated unilaterally by various quarters